Sleep discrepancy and brain glucose metabolism in community-dwelling older adults - Nadia Soh; Michael Weinborn; James D. Doecke; Rodrigo Canovas; Vincent Doré; Ying Xia; Jurgen Fripp; Kevin Taddei; Romola S. Bucks; Hamid R. Sohrabi; Ralph N. Martins; Melissa Ree; et al. (Aging Brain)
Sleep discrepancy (negative discrepancy reflects worse self-reported sleep than objective measures, such as actigraphy, and positive discrepancy the opposite) has been linked to adverse health outcomes. This study is first to investigate the relationship between sleep discrepancy and brain glucose metabolism (assessed globally and regionally via positron emission tomography), and to evaluate the contribution of insomnia severity and depressive symptoms to any associations. Using data from cognitively unimpaired community-dwelling older adults (N = 68), cluster analysis was used to characterise sleep discrepancy (for total sleep time (TST), wake after sleep onset (WASO), and sleep efficiency (SE)), and logistic regression was used to explore sleep discrepancy’s associations with brain glucose metabolism, while controlling for insomnia severity and depressive symptoms. Lower glucose metabolism across multiple brain regions was associated with negative discrepancy for WASO and SE, and positive discrepancy for WASO only (large effect sizes; β ≥ 0.5). Higher glucose metabolism in the superior parietal and posterior cingulate regions was associated with negative discrepancy for TST (large effect sizes; β ≥ 0.5). These associations remained when controlling for insomnia severity and depressive symptoms, suggesting a unique role of sleep discrepancy as a potential early behavioural marker of brain health.